THE EFFECT OF DIGITAL GAME ADDICTION ON AGGRESSION IN SCHOOLAGE CHILDREN. - Köse, Semra; Ayran, Gülsün; Aslan, İlyas (Karya Journal of Health Science, 2024)
Objective: This study was conducted to determine the impact of digital game addiction on aggression in school-age children. Method: This descriptive and cross-sectional study was conducted in January-June 2023 with children aged 10-11 years studying in secondary schools in Batman. The study was completed with 300 children who met the research criteria. Data were collected by distributing the questionnaire form, Digital Game Addiction Scale for Children and Aggression Scale to the children whose parental consent was obtained in a time period that would not disrupt the class hours. In the evaluation of the data; percentages, averages, t test, Anova, Bonferonni, Pearson Correlation analyzes were used. Results: It was determined that 52% of the students participating in the study were male and 57.3% were 11 years old. The digital game addictions and aggression of male students, those whose mothers and fathers are civil servants, those who have a tablet/computer/phone, those who play games for 4 hours or more a day with a tablet/computer/phone, and those who mostly prefer computers to play games are statistically significant. There was a significant positive correlation between children's digital game addiction and aggression (p<0.05). Conclusion: It was determined that as students' digital game addiction levels increased, their aggression levels increased. In addition, as the daily playing time of the students increased, their digital game addiction and aggression levels also increased.